Attracting managers to international companies based in Poland - Przytuła, Sylwia (Uniwersytet Ekonomiczny we Wrocławiu, 2010)
This article presents survey results concerning the recruitment of managers for the international companies operating in Poland. Taking into account the triad model, the article shows the forms of recruitment, selection techniques and placement methods of managers to companies which come from Asian, American and European sphere of culture. The author presents the meaning of cultural factors in staffing for the key positions in surveyed firms.
Argumenta Oeconomica, 2010, Nr 2 (25), s. 51-66
Keywords: managers; international company; placement; recruitment; expatriates; selection